Jakartan Slang as a Generational Identity Marker and the Reduced Use of Javanese in Peer Interaction among Generation Z Students at Universitas Negeri Semarang - Vania Aurellia Harinda Artamevia; Ninuk Sholikhah Akhiroh (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
The increasing use of Jakartan slang among Generation Z has become a visible feature of youth communication in Indonesian university settings. While previous studies have examined the forms, meanings, and social functions of slang, less attention has been given to how slang shapes generational identity and affects the use of local languages in campus peer interaction. This study examines Jakartan slang as a generational identity marker among Generation Z students at the Faculty of Social and Political Sciences, Universitas Negeri Semarang, and explores its implications for the reduced use of Javanese in selected peer interactions. Using a descriptive qualitative approach, the study draws on semi-structured interviews with 10 students, qualitative questionnaire responses from 10 Javanese-speaking students, and unstructured observation in campus-related settings. The data were analyzed thematically and interpreted through Social Identity Theory, particularly the concepts of social categorization, social identification, and social comparison. The findings show that Jakartan slang functions not only as an informal communicative style but also as a social resource through which students construct peer belonging, align themselves with modern youth culture, and distinguish their generation from older or more local linguistic repertoires. Among Javanese-speaking participants, Jakartan slang is used because it is perceived as practical, inclusive, socially current, and widely understood in multilingual peer groups. This practice may reduce the space for Javanese in certain informal campus interactions, although the findings do not indicate a general decline of Javanese at UNNES or in broader Javanese society. The study contributes to sociolinguistic discussions by showing that slang, local language use, and generational identity are closely connected through peer-group dynamics, digital culture, and the symbolic value attached to language in multilingual university contexts.